The Importance of Spin State in Chiral Supramolecular Electronics - Garcia, Ana M.; Martínez, Gabriel; Ruiz-Carretero, Amparo (Frontiers in Chemistry, 2021)
The field of spintronics explores how magnetic fields can influence the properties of organic molecules by controlling their spins. In this sense, organic materials are very attractive since they have small spin-orbit coupling, allowing long-range spin transport along their structures. Usually, the small spin-orbit coupling means that organic materials cannot be used for spin injection, requiring ferromagnetic electrodes. However, chiral molecules have been demonstrated to behave as spin filter materials upon light illumination in the phenomenon described as chirality-induced spin selectivity (CISS) effect. This means that electrons of certain spin can go through chiral assemblies of molecules preferentially in one direction depending on their handedness. This is possible because the broken symmetry in chiral molecules couples with the electron’s spin and its linear momentum so the molecules transmit the one preferred spin. In this respect, chiral semiconductors have great potential in the field of organic electronics since when changer carriers are created, a preferred spin could be transmitted through a determined handedness structure. The exploration of the CISS effect in chiral supramolecular semiconductors could add greatly to the efforts made by the organic electronics community since charge recombination could be prevented and charge transport improved when the spins are preferentially guided in one specific direction. This review outlines the advances made in supramolecular chiral semiconductors regarding their spin state and the influence on the final electronic properties. Different chiral materials assembled through diverse supramolecular chemistry strategies will be discussed, and the role of the spin state in their properties reviewed.